Cryptococcus neoformans meningoencephalitis in an HIV-seronegative patient: A case report - Kızılaslan, Deniz; Erdoğan, Cem; Yılmaz, Ece Aslı; Karaaslan, Pelin (Springer, 2020)
Background Cryptococcal meningoencephalitis is an important opportunistic infection that usually affects immunocompromised patients. Usually seen in HIV (human immune deficiency virus)-seropositive patients, Cryptococcus neoformans may also be seen in patients who receive immune-suppressing glucocorticoid treatment, undergo solid organ transplant, have cancer, especially hematologic malignancies, and liver failure (Messina et al. 2017). However, in rare cases, Cryptococcal meningoencephalitis can be seen in suspected immunocompetent patients as well.
Keywords: Cryptococcus Neoformans; Meningoencephalitis; HIV; Seronegative Patient